Organoruthenium‐Containing Heteropoly‐23‐Tungstate Family [{Ru(L)}2(α‐XW11O39)2WO2]m– (L = benzene, p‐cymene; X = GeIV, SiIV, m = 10; BIII, m = 12)1. Issue 10 (8th February 2013) - Nsouli, Nadeen H.; Chubarova, Elena V.; Al‐Oweini, Rami; Bassil, Bassem S.; Sadakane, Masahiro; Kortz, Ulrich
Abstract: A family of {Ru(arene)} 2+ ‐containing heteropolytungstates of general formula [{Ru(L)}2 (α‐XW11 O39 )2 WO2 ] m – (L = benzene, p ‐cymene; X = Ge IV, Si IV, m = 10; X = B III, m = 12) has been prepared in aqueous acidic medium (pH ≈ 4). The 1:1 interaction of [Ru(C6 H6 )Cl2 ]2 or [Ru( p ‐cymene)Cl2 ]2 with [β2 ‐GeW11 O39 ] 8– led to the formation of [{Ru(benzene)}2 (GeW11 O39 )2 WO2 ] 10– (1 ) and [{Ru( p ‐cymene)}2 (GeW11 O39 )2 WO2 ] 10– (2 ), respectively. Replacing [β2 ‐GeW11 O39 ] 8– by [α‐SiW11 O39 ] 8– resulted in [{Ru(benzene)}2 (SiW11 O39 )2 WO2 ] 10– (3 ) and [{Ru( p ‐cymene)}2 (SiW11 O39 )2 WO2 ][SiW12 O40 ]0.5 12– (4 ), respectively. The reaction of [α‐HBW11 O39 ] 8– with the respective {Ru(arene)} 2+ ‐containing precursors resulted in polyanions [{Ru(benzene)}2 (HBW11 O39 )2 WO2 ] 10– (5 ) and [{Ru( p ‐cymene)}2 (HBW11 O39 )2 WO2 ] 10– (6 ), respectively. Single‐crystal XRD analysis of the hydrated salts of1 –6 revealed that these species comprise two Keggin fragments, [{Ru(L)}α‐XW11 O39 ] 6– (L = benzene, p ‐cymene; X = Ge IV, Si IV ) for polyanions1 –4 and [{Ru(L)}α‐HBW11 O39 ] 6– (L = benzene, p ‐cymene) for5 and6, connected via a cis ‐dioxo WO2 2+ unit. In addition, the heteropolytungstates were characterized by thermogravimetric analysis, IR spectroscopy, elemental analysis, and solution electrochemical studies. Abstract : Six organoruthenium‐containing heteropoly‐23‐tungstates [{Ru(L)}2 (α‐XW11 O39 )2 WO2 ]m– (L = benzene, p ‐cymene; X = Ge IV, Si IV, m = 10; X = B III, m = 12) have been synthesized and characterized by X‐ray diffraction, thermogravimetric analysis, IR spectroscopy, and solution electrochemistry.